Bacillus anthracis‐Like Strain‐Carrying Pseudomonas FPVA Gene Occurs as Endophyte in Vegetables. Issue 1 (23rd January 2014) - Srinath, R.; Siva, R.; Babu, S.
Abstract We isolated Bacillus anthracis‐like strain from internal tissues of marketed vegetables (onion and cucumber). Further analysis of the pigment‐producing cucumber strain implicates a possible horizontal gene transfer of pyoverdine (pvd) uptake receptor gene from Pseudomonas sp. augmenting Bacillus strain's ability to infect and survive in cucumber internal tissues. To our knowledge, the animal anthrax causing bacterium has not been reported previously in agricultural produce and hence we propose that acquired virulence gene provides enhanced survivability within alternate hosts. Thus, we present the first report of this pathogen being isolated from internal tissues of marketed vegetables. Practical Application The observation of Bacillus anthracis‐like strain in onion and cucumber tissues indicates changing ecology of this pathogenic bacterium. This warrants proper pre‐harvest as well as post‐harvest handling as these vegetables are consumed as fresh salads also. The results of the study will help in developing strategies to avoid contamination from farm to the dining table.